Statistical approach in analyzing emf data - Nooraima Hafiza Mahmuri (2023)
This project is analysis of Electromagnetic fields (EMF) data using Statistical Technique. To implement Statistical Technique, it is vital to identify statistical parameters in order to study the constructed or developed 2D distributions which are obtained from availableEMF data.